A representação da mulher no cinema: uma análise do filme Barbie (2023) e as expressões da vida da mulher contemporânea - Lopes, Gabrielle dos Santos (2024)
Studies on cinema and History are considerably recent. In the beginning, the ways of doing History were directly linked to written documentary sources, it was It was only in the 20th century, with the Annales movement, that the concept of historical source was debated and expanded. The History of Art has been known for some time, but the relationship between it and Visual Culture, of which cinema is a part, were kept apart for many years, therefore, the The study of their intercession is also recent. Despite the few works carried out on this subject, some valid contributions have already been made and published by scholars in the field of History and Art. Hollywood cinema, from the beginning of its emergence, sought to represent aspects of human life. Over time, these representations were transformed and became if necessary, deepen them and attribute meanings to them. Today, audiovisual productions are very differ from the older ones and despite noticeable permanence in the representation of women, Some audiovisual productions introduce new forms of think about the issue of women in history. Women were largely supporting actors, or mere extras in the productions, his characters had few or even no lines. They played mothers, governesses, housewives and addressed subjects that added nothing to the unfolding of the story counted. Furthermore, acting as an actress itself was not considered a profession, On the contrary, women who chose to dedicate themselves to the art of interpretation were seen as prostitutes. Role that, due to the objectification of their bodies, also performed in front of the cameras.